Internalization of Entrepreneurial Prophetic Communication Education at Home Foundation of Entrepreneurship and Self-Development (RKPD) Bandung - Zainal Sofi, Yofi Nur; Cepian (Yayasan Mentari Madani, 2023)
This study aims to explain the internalization of prophetic entrepreneurial communication of the RKPD Foundation through the Foundation's program in volunteer empowerment. Qur'an-based prophetic communication is communication that refers to the prophetic communication pattern of Muhammad (peace be upon him) loaded with egalitarian values, tolerance, gentleness, generosity, and spirituality. This theory constructs a social transformation that promotes divine and prophetic values through the relationship between humanization, liberation, and transcendence to dehumanist reality. Proof of the success of this theory is by looking at the history of the Prophet in realizing civil society through three dimensions, namely 1) humanization, such as egalitarian, defending the weak, deliberation, and tolerance, 2) liberation, such as anti-discrimination, easy forgiveness, freedom of society, 3) transcendence, such as piety to Allah Almighty, making the Qur'an as a guideline, and recognizing the Prophet Muhammad as a messenger of God as well as a leader. The theories used in this study are entrepreunerial theory and SOR theory and the author also incorporates prophetic communication approaches into entrepreneurial studies. Researchers use a cutative approach with explanatory purposes. The data collection techniques used were in-depth interviews as well as documentation. The results of this study show that the RKPD Foundation uses the entrepreneurial process in the pattern of internalizing prophetic communication in the form of constructive Foundation work programs such as volunteer character, providing s1, s2, s3 scholarships, school scholarships to pursue packages for street children, Quran reading learning programs, Quran memorization programs, building mosques and well endowments, caring for orphans, , spiritual formation of volunteers, Islamic boarding school support system All of these programs are used by the RKPD Foundation to empower their communities, especially Islamic communities